First measurement of the CP-violating phase in B0s→J/ψ(→e+e−)ϕ decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; et al. (The European physical journal. C, Particles and fields, 2021)
A flavour-tagged time-dependent angular analysis of $${{B} ^0_{s}} \!\rightarrow {{J /\psi }} \phi $$decays is presented where the $${J /\psi }$$meson is reconstructed through its decay to an ^+e ^-$$pair. The analysis uses a sample of pp collision data recorded with the LHCb experiment at centre-of-mass energies of 7 and $$8\text {\,Te V} $$, corresponding to an integrated luminosity of ^+e ^-$$pair in the final state. The results are consistent with previous measurements in other channels and with the Standard Model predictions.
Gesehen am 10.02.2022
Im Titel sind "0" und "+" und "-" hochgestellt, "s" tiefgestellt